P.001 Rate of cognitive decline in dementias in patients from rural and remote Saskatchewan. (June 2019) - Shahab, IU; Kirk, A; Karunanayake, C; O'Connell, M; Morgan, D
Abstract : Background: To determine whether there is a difference in the average annual rate of decline in Mini Mental Status Examination (MMSE) scores between those with Alzheimer's disease, vascular dementia, frontotemporal dementia and dementia with Lewy bodies. Methods: We conducted a retrospective chart review of 225 consecutive patients with dementia who attended the Rural and Remote Memory Clinic in Saskatoon, Saskatchewan. The data collected included MMSE scores and demographic information. Statistical analysis with ANOVA compared the average the annual rate of decline in MMSE score between patients with different types of dementia. Results: There was no statistically significant difference in the rate of MMSE score decline between these groups. Patients with frontotemporal dementia and vascular dementia were referred to the clinic at younger ages than those with Alzheimer's disease and dementia with Lewy bodies. Conclusions: The rate of decline in MMSE did not differ between these four types of dementia. Patients with frontotemporal dementia and vascular dementia often experience cognitive decline earlier in life than those with Alzheimer's disease and dementia with Lewy bodies.